Networks of international co-authorship in journal articles about Antarctic research, 1998–2015 - Jang, Duckhee; Doh, Soogwan; Choi, Yongjin (Polar Research, 2020)
This study seeks insight into the social structure of Antarctic research from 1998 to 2015 by examining peer-reviewed journal articles listed in the Science Citation Index of the Web of Science database. This study identifies leading countries in peer-reviewed journal article output and applies social network analysis methods to identify countries where authors are collaborating with those affiliated with organizations in different countries. The results show that the number of publications on Antarctica and the proportion of international research collaboration increased from 23.0 to 33.2% during the period of time being considered. The number of articles published by authors affiliated with institutions in emerging countries such as China, Turkey, Brazil and South Korea rose, whereas the proportion of articles published by authors affiliated with institutions in the United States decreased. The largest proportion of academic publications pertaining to Antarctic research was within the natural sciences. Within this broad field, the majority of publications fell within Earth and related environmental sciences and the biological sciences. Social network analysis shows that Antarctic research moved towards a network, in which researchers are internationally more connected than ever before, with countries such as the United States, the United Kingdom, Germany, France and Australia in central positions. Sweden, Belgium and the Netherlands did not account for a high percentage of academic contributions but were still notable for their multinational collaborative research.
Keywords: Antarktis; forskning; publikasjoner; vitenskap

On the long-ignored scientific achievements of the Belgica expedition 1897–1899 - De Deckker, Patrick (Polar Research, 2018)
The Belgica expedition, which left Belgium in August 1897, was the first to spend 13 months continuously in Antarctic waters, before returning in late 1899. This was not only an exploratory venture, as new lands and oceans were charted, but more importantly it was an exceptional and successful scientific voyage. After the return of the expedition, a vast array of scientific data was processed and eventually 92 publications in some nine volumes funded by the Belgica Commission appeared over 40 years as a series called Résultats du voyage de la Belgica en 1897–99 sous le commandement de A. de Gerlache de Gomery – rapports scientifiques. Disappointingly, those significant results have been mostly ignored in the scientific literature and the paper here aims to inform scientists of the achievements of the Belgica expedition and where to obtain the information. Many of the climatological and oceanographic data obtained by the expeditioners ought to be examined in line with the changes that are occurring today in the Antarctic Peninsula region as a result of global warming. Some of the Belgica data form an important database to critically assess environmental changes over 120 years in the region of the Antarctic Peninsula.
Keywords: Antarktis; Belgica ekspedisjon; glasiologi; global oppvarming; klimaendringer; klimatologi; meteorologi; miljøendringer; oppdagelsesreiser; oseanografi; vitenskap

Facing the climate change conundrum at the South Pole: actors’ perspectives on the implications of global warming for Chilean Antarctic governance - Gladkova, Ekaterina; Blanco-Wells, Gustavo; Nahuelhual, Laura (Polar Research, 2018)
Antarctica is recognized as being geopolitically and scientifically important, and as one of the regions with the greatest potential to affect and be affected by global climate change. Still, little is known in practice about how climate change will be handled within the main governance framework of the continent: the Antarctic Treaty System (ATS). Using qualitative interviews, participant observations and policy document analysis, this paper explores the perspectives of Chilean scientific, political and non-governmental actors regarding the implications of climate change for the current Antarctic governance framework. Results corroborate a misalignment of the climate change agenda and the ATS, stemming from the divergent views displayed by a wide network of actors. From the interviews, two predominant visions emerge: (i) climate change as an opportunity, where actors recognize the role of Antarctica in regulating global climate and stress greater opportunities to conduct Antarctic-based climate change research, the need for strategic international collaboration, and the reinforcement of Chile’s position in Antarctica through science; (ii) climate change as a burden where actors acknowledge climate change as a global problem, largely external to Antarctica, express disbelief regarding the effectiveness of local actions to tackle climate change and do not associate with climate change governance. The study concludes that climate change may become a dividing, rather than a unifying, field of action in Chilean Antarctic governance, reinforcing previously existing geopolitical tendencies.
Keywords: Antarktis; Antarktistraktaten; geopolitikk; klimaendringer; vitenskap

Revisiting perceptions and evolving culture: a community dialogue on women in polar research - Starkweather, Sandra; Seag, M; Lee, O; Pope, A (Polar Research, 2018)
Women have made outstanding contributions to polar research in recent decades, though full engagement may be hindered by persistent inequities, including notably the prevalence of workplace harassment. Remote field settings, such as those pervasive in polar research, have been identified as particularly susceptible to cultures of harassment. It was therefore timely at the Polar 2018 Open Science Conference in Davos, Switzerland, to convene a discussion focused on women’s perspectives and experiences. A panel discussion—“From Entering the Field to Taking the Helm: Perspectives of Women in Polar Research”—took place on 20 June 2018 and featured five women undertaking work from marine biotechnology to organizational leadership, across career levels. Over 300 conference attendees joined the lunchtime panel. The panellists’ perspectives on historical barriers, current challenges and future prospects revealed that while challenges persist, experiences vary greatly. Audience engagement underscored the need to sustain dialogue at polar meetings, to bring visibility to the statistics related to workplace harassment and to encourage polar science organizations to assume leadership on promoting equitable workplace culture.
Keywords: Antarktis; arbeidsmiljø; kjønn; kultur; likestilling; polarforskning; sosiologi; trakassering; vitenskap

Naturen 1916 Roald Amundsens sydpolsfærd og dens videnskabelige resultater (Naturen, 2016)
Efterat kaptein James Ross i 1841 hadde opdaget det sydpolare eller antarktiske fastland og den store isbarriere under sin seilas i det hav som efter ham har faat navn av Ross-Havet, blev den øvrige del av dette fastland fremdeles ukjendt indtil 1898. Fra dette aar av har en række ekspeditioner med større og mindre held forsøkt at finde beliggenheten av det antarktiske fastlands kyster, og av disse har nogen opnaadd at trænge ind i det indre, endog like til sydpolen. Imidlertid er der endnu store strækninger hvor havisen har stængt seilasen og gjort det umulig at naa ind til det faste land.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; historie; oppdagelsesreiser; vitenskap

Delivering 21st century Antarctic and Southern Ocean science - Kennicutt, Mahlon C I I; Kim, Yeadong; Rogan-Finnemore, Michelle; Anandakrishnan, Sridhar; Chown, Steven L; Colwell, Steven (Antarctic Science, 2016)
The Antarctic Roadmap Challenges (ARC) project identified critical requirements to deliver high priority Antarctic research in the 21st century. The ARC project addressed the challenges of enabling technologies, facilitating access, providing logistics and infrastructure, and capitalizing on international co-operation. Technological requirements include: i) innovative automated in situ observing systems, sensors and interoperable platforms (including power demands), ii) realistic and holistic numerical models, iii) enhanced remote sensing and sensors, iv) expanded sample collection and retrieval technologies, and v) greater cyber-infrastructure to process ‘big data’ collection, transmission and analyses while promoting data accessibility. These technologies must be widely available, performance and reliability must be improved and technologies used elsewhere must be applied to the Antarctic. Considerable Antarctic research is field-based, making access to vital geographical targets essential. Future research will require continent- and ocean-wide environmentally responsible access to coastal and interior Antarctica and the Southern Ocean. Year-round access is indispensable. The cost of future Antarctic science is great but there are opportunities for all to participate commensurate with national resources, expertise and interests. The scope of future Antarctic research will necessitate enhanced and inventive interdisciplinary and international collaborations. The full promise of Antarctic science will only be realized if nations act together.
Keywords: Antarktis; forskning; vitenskap

Reading and thinking about International Polar Years: five recent books - Carlson, Dave (Polar Research, 2013)
Within the polar science community the Polar (and Geophysical) Years represent signal events. We often read, largely within geoscience literature, that those events represented positive and dramatic steps forward in international science. From five recent books - two historical compilations and three personal narratives - augmented by interviews with a few key participants, a more cautious picture emerges, of remarkable successes but also of occasional or even persistent missteps and deficiencies. An improved understanding of the IPY concept and experience can provide useful guidance for future polar and global science. Keywords: International Polar Year; International Geophysical Year; international science; history of polar science.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); IPY; bokanmeldelser; internasjonal; politikk; samarbeid; vitenskap

Trends in Antarctic ecological research in Latin America shown by publications in international journals - Stotz, Gisela C; Salgado-Luarte, Cristian; Rios, Rodrigo S; Acuña-Rodriguez, Ian S; Carrasco-Urra, Fernando; Molina-Montenegro, Marco A; Gianoli, Ernesto (Polar Research, 2013)
Antarctica is a highly interesting region for ecologists because of its extreme climatic conditions and the uniqueness of its species. In this article, we describe the trends in Antarctic ecological research participation by Latin American countries. In a survey of articles indexed by the ISI Web of Science, we searched under the categories ‘‘Ecology,’’ ‘‘Biodiversity Conservation’’ and ‘‘Evolutionary Biology’’ and found a total of 254 research articles published by Latin American countries. We classified these articles according to the country of affiliation, kingdom of the study species, level of biological organization and environment. Our main finding is that there is a steady increase in the relative contribution of Latin American countries to Antarctic ecological research. Within each category, we found that marine studies are more common than terrestrial studies. Between the different kingdoms, most studies focus on animals and most studies use a community approach. The leading countries in terms of productivity were Argentina, Chile and Brazil, with Argentina showing the highest rate of increase. Keywords: Antarctica; Argentina; Brazil; Chile; research trends; scientific productivity.
Keywords: Antarktis; biodiversitet; forskning; vitenskap; økologi

Leadership in politics and science within the Antarctic Treaty - Dudeney, John R; Walton, David W H (Polar Research, 2012)
For over 50 years the Antarctic has been governed through the Antarctic Treaty, an international agreement now between 49 nations of whom 28 Consultative Parties (CPs) undertake the management role. Ostensibly, these Parties have qualified for their position on scientific grounds, though diplomacy also plays a major role. This paper uses counts of policy papers and science publications to assess the political and scientific outputs of all CPs over the last 18 years. We show that a subset of the original 12 Treaty signatories, consisting of the seven claimant nations, the USA and Russia, not only set the political agenda for the continent but also provide most of the science, with those CPs producing the most science generally having the greatest political influence. None of the later signatories to the Treaty appear to play a major role in managing Antarctica compared with this group, with half of all CPs collectively producing only 7% of the policy papers. Although acceptance as a CP requires demonstration of a substantial scientific programme, the Treaty has no formal mechanism to review whether a CP continues to meet this criterion. As a first step to addressing this deficiency, we encourage the CPs collectively to resolve to hold regular international peer reviews of their individual science programmes and to make the results available to the other CPs. Keywords: Governance; claimant states; Antarctic policy; scientific publications.
Keywords: Antarktis; Antarktistraktaten; forvaltning; politikk; vitenskap

Review of Legacies and change in polar sciences: historical, legal and political reflections on the International Polar Year, edited by JM Shadian & M Tennberg - Dodds, Klaus (Polar Research, 2010)
The International Polar Year (IPY) of 2007–09 was an international scientific enterprise that encompassed all polar regions, and built on the legacies bequeathed by earlier endeavours stretching back to the late 19th century. The first such venture was initiated in 1882–83, the second was in 1932–33 and the last, the International Geophysical Year (IGY), occurred in 1957–58, and involved thousands of scientists working inter alia in the polar continent. Activity in the Arctic, for geopolitical reasons, was rather more limited, and was certainly not epitomized by free and unfettered scientific investigation. Sponsored by the International Council for Science, the most recent IPY was noteworthy for its explicit bi-polar focus, and its integration of the humanities and social sciences with the physical and environmental sciences. The role of indigenous communities was also notable in Arctic-based projects, a development that would have been inconceivable during the IGY. As with the IGY, however, a spectacular event in one of the theatres of scientific interest grabbed world headlines: in 1957 it was Sputnik orbiting the Earth, and in 2007 it was a Russian submersible planting a flag on the bottom of the central Arctic Ocean basin.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); bokanmeldelser; forskning; geopolitikk; internasjonal; polarområdene; samarbeid; vitenskap

From the editor: halfway through the IPY—halfway for an Antarctic traverse - Goldman, Helle V (Polar Research, 2008)
April is here and we have just passed the midpoint of the International Polar Year (IPY), which began on 1 March 2007 and will conclude on 1 March 2009. The “year” stretches over 24 months to accommodate two summer field seasons in both polar regions. The northern summer is fast approaching, and scientists who will undertake a second IPY summer season in the Arctic are making their final preparations. At the opposite end of the planet, summer is over and scientists have wrapped up the first IPY field season. Those whose projects will carry on for a second summer season will have to wait until late this year to resume work in Antarctica.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norsk Polarinstitutt; ekspedisjoner; forskning; polarområdene; vitenskap

Norway and past International Polar Years—a historical account - Bones, Stian (Polar Research, 2007)
Surveying Norway’s role in past International Polar Years (IPYs), this essay by historian Stian Bones contributes to a broader understanding of Norway as a “polar nation”. He describes the strengths of Norway’s scientific traditions in the polar regions, and examines the varying motivations driving Norwegian involvement in the first three IPYs: 1882–83, 1932–33 and 1957–58 (also known as the International Geophysical Year).
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norge; historie; polarområdene; vitenskap

Fra selfangstskuter til vitenskapelige ekspedisjonsskip. Svend Foyn og ishavsekspansjonen fra Sør-Norge - Christensen, Olav (Norsk sjøfartsmuseum. Årbok, 2007)
Publisher: Norsk sjøfartsmuseum Place: Oslo
Keywords: Carl Anton Larsen; Nordmenn; Sørishavet; Vestfold; ekspedisjoner; fangst; hvalfangere; hvalfangst; oppdagelsesreiser; polarområdene; vitenskap

Polar Research evolves, and Norway and the IPY - Goldman, Helle V (Polar Research, 2007)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norge; Norsk Polarinstitutt; ekspedisjoner; forskning; polarområdene; vitenskap

Antarctic science in a historical perspective: changing roles and functional development - Indreeide, Thor Vidar (International Challenges, 1990)
Keywords: Antarktis; forskning; historie; vitenskap

Arctic and Antarctic : current problems in the Polar region - Sollie, Finn (Cooperation and Conflict, 1969)
Sætrykk
Keywords: Antarktis; Antarktistraktaten; polarområdene; politikk; utforskning; vitenskap

Arktis og Antarktis : aktuelle problemstillinger - Sollie, Finn (Internasjonal politikk, 1968)
Keywords: Antarktis; Antarktistraktaten; polarområdene; politikk; utforskning; vitenskap

Lys over "tåkeheimen" i sør: den videnskapelige serie fra Lars Christensens ekspedisjoner avlsuttet - Isachsen, Fridtjov (Norsk hvalfangst-tidende, 1962)
Keywords: Antarktis; Sørishavet; forskning; litteratur; naturvitenskap; vitenskap

Antarktis, der snøfokket pisker i juli : om ismassene rundt Sydpolen smelter, stiger verdenshavene med 30 meter : "Norsel"-ekspedisjonen får stor betydning for vitenskapen - [Roer, Nils] (Nå, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsel (skip); Norsk-britisk-svenske antarktisekspedisjon; Sydpolen; vitenskap

Den norsk-brittisk-svenska antarktisexpeditionen 1949-52. En översikt av färder och arbeten intill mitten av december - Liljequist, Gösta H (Ymer, 1951)
Publisher: Svenska Sällskapet för antropologi och geografi
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskningsprogram; vitenskap

Til hvalfangerne: videnskabelige samlerarbeide - Holtedahl, Olaf (Norsk hvalfangst-tidende, 1928)
Keywords: Antarktis; Sørishavet; museer; vitenskap